Dekonstruksi Hubungan Kemitraan Pada Ekonomi Gig: Tinjauan Yuridis Terhadap Kontrol Algoritmik Dan Kebebasan Semu Dalam Kontrak - Naufal Hibatul Wafi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The expansion of the gig economy business model in Indonesia has generated complex legal issues concerning the validity of the “partner” status assigned to online transportation drivers. This classification places drivers outside the protective framework of Law No. 13 of 2003 on Manpower, resulting in the deprivation of fundamental labor rights such as minimum wages and social security. This study examines the legal validity of partnership agreements under Article 1320 of the Indonesian Civil Code, with particular emphasis on defects of consent, and compares the findings with the rationale of the Uber BV v Aslam decision in the United Kingdom. Employing a normative juridical method with statutory, conceptual, and comparative law approaches, the study finds that existing partnership agreements suffer from fundamental legal defects due to violations of the principle of contractual balance and the presence of abuse of circumstances (misbruik van omstandigheden), both economically and psychologically. Furthermore, algorithmic control exercised by platform operators fulfills the element of authority (gezag) that characterizes an employment relationship, rendering the “partner” status legally invalid. Accordingly, the study recommends the adoption of a sui generis regulatory framework to ensure social protection for gig workers while preserving labor market flexibility.